Engaging tourists with museums in the destination Lisbon - Loureiro, S. M. C.; Ferreira, E. S. (Proceedings of ANZMAC 2016 - Marketing in a Post-Disciplinary Era, 2016)
The aim of this study is to analyze the relationships among the concepts of serious leisure and museum prestige on engagement with museums, pleasant emotions, memory, and word-of-mouth among Lisbon tourists. Findings reveal that reflective motivations are one important driver of engagement. Be engaged with museums lead to create positive emotions and memories, which, in turn, contribute to the willingness to communicate and recommend the Lisbon museums to others.